(untitled) (International Journal of Current Engineering and Technology, 2014)
An Orchestrator coordinates and control computations in parallel and sequential computing nodes. The paper presents an Orchestrator framework for automation of multiple robots. The orchestrator controlling mechanism is adaptive and flexible. According to application, it is able to decide the invoking sequence of robots. The proposed framework also manages service failures. The framework is implemented using RMI, multithreading and RS-232 standard in Java.